DETERMINANT FACTORS FOR UNINTENDED PREGNANCY IN BALI PROVINCE - Putu Ayu Indrayathi; Putu Erma Pradnyani; Ngakan Putu Anom Harjana; Luh Putu Sinthya Ulandari; Anastasia Septya Titisari; Luh Kadek Ratih Swandewi (Universitas Airlangga, 2022)
Bali Province has the lowest unmet need achievement, namely 8.1%, meaning that it has a low-value gap between the availability of contraceptive services and the needs of the community. This study analyzed the factors that influence the incidence of unintended pregnancy among childbearing-age women in Bali. This research is a secondary data analysis from the Program Performance and Accountability Survey (PPAS) of the National Population and Family Planning Board in 2019. The variables studied were selected from the PPAS’s Women data, with 1,214 samples of married fertile women aged 15-59 years in Bali. Multivariate analysis in the form of a logistic regression test is carried out to estimate factors that affect unintended pregnancy incidence in childbearing-age women in Bali. Factors influencing unintended pregnancy are age and having heard of family planning, understanding birth control, understanding population issues, and having listened to adolescent reproductive health. The multivariate analysis shown that age and having heard of family planning are two factors that significantly influence unintended pregnancy. Two factors that influence unintended pregnancy in Bali are age and having heard about family planning. Therefore, cross-sector engagement is required to provide a family planning program to the targeted fertile women's age found in this research to improve women's exposure to the program.